ON ZOROASTRIANISM IN DAGESTAN - Asatran, Garnik Serobovic (History, Archeology and Ethnography of the Caucasus, 2024)
This article explores possible traces of Zoroastrianism in Dagestan within the context of the pre-Islamic religious landscape of the North Caucasus. It presents methodological principles for identifying Middle Iranian lexemes with potential religious connotations in Dagestani languages, particularly Avar. The relevant data are presented as individual lemmas indicating, directly or indirectly, the spread of the religion of the Magi in Dagestan, apparently in a limited format. The study provides a detailed analysis of each lexeme related to the Middle Iranian period based on linguistic parameters. Additionally, it considers some Armenisms and Iranisms coming from Armenian and Scythian-Sarmatian milieus, though not directly related to Zoroastrianism. Meanwhile, if terms manifesting Christian influences have pronounced religious guise (such as designations of Christian objects and symbols, like the cross), and are thus easily identifiable, most purported Zoroastrian terms lack explicit religious markers, making them difficult to recognize without strict adherence to specific methodological principles. The hypothesis of a Zoroastrian past in Dagestan, despite the near-total absence of religious monuments with Zoroastrian attribution, is largely based on Emile Benveniste’s thesis conditioning a Zoroastrian inheritance for a particular ethnic community on the obligatory presence in the language of a number of diagnostic terms (or at least one of them) that reflect Zoroastrian dogma. The article also includes an appendix discussing the concept of the mosque in North Caucasian languages, providing materials and generalizations relevant to the main topic.
Keywords: Zoroastrianism in Dagestan; Middle Iranian elements in the Dagestan languages; Christianity in Dagestan; Armenisms in the Dagestan languages; concept of “mosque” in the North Caucasus; “prophet” in Avaro-Andic; “sorceress” in Avar